Forest fires in the Annaba subdivision during the colonial period - the fires of 1890 in the arrondissement of Guelma as a model- - meddour, khemissa (The Algerian Historical Journal, 2026)
The French colonial administration realized the importance of forest cover in the Annaba division, including the important forest regions that are in Guelma department, which is characterized by its density and diversity. This is what prompted the French administration to organize a forest exploitation process and benefit from its products at the expense of the forest tribes that were subjected to the expropriation of large properties through the application of various expropriation laws or as a result of holding the Muslim population responsible for the series of fires that it witnessed during successive periods by imposing various penalties such as fines, imprisonment, and limiting pastoral areas and Others that often end with the dispossession of forest regions, which we aim to highlight by monitoring the most important forest fires during the year 1890 in the most important forests of the Guelma region and to determine the extent of the responsibility of the population for this process, based on the study and analysis of archival documents related to the series of fires witnessed by the department during this period and preserved in the archives of Aix-en-Provence in France.